Analysis of the Impact of E-Learning-Based Religious Learning on Student Character - Hanif, Aminul Zafirah (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
The rapid growth of e-learning platforms has transformed the landscape of education, including religious education, which has traditionally been delivered in classroom settings. This shift towards digital learning has raised important questions regarding its impact on students' character development, particularly in the context of religious studies. The purpose of this study is to analyze the effects of e-learning-based religious education on students' character development by reviewing relevant literature and synthesizing existing research. This qualitative study uses a literature review methodology to gather data from various academic sources, focusing on the benefits and challenges of e-learning in religious education. The data was analyzed through thematic analysis to identify patterns and draw conclusions about the relationship between e-learning and character education. The findings reveal that e-learning can have both positive and negative impacts on character development. On the one hand, it promotes autonomy, self-regulation, and accessibility to diverse religious teachings, fostering critical thinking, empathy, and moral reasoning. On the other hand, the lack of face-to-face interactions can lead to feelings of isolation, and the over-reliance on digital platforms can result in distractions, reducing students' focus on moral engagement. To maximize the benefits of e-learning, a blended learning approach combining online learning with traditional face-to-face interactions is recommended. This study provides valuable insights for educators and policymakers seeking to optimize the use of e-learning in religious education for effective character development.